Performance evaluation of the development of eco-cultural tourism in Fujian Province based on the method of fuzzy comprehensive evaluation - Zheng, Qiuqin; Chen, Qiuhua; Kong, Deyi (Frontiers in Environmental Science, 2022)
The performance evaluation serves as a crucial means of examining the economic, ecological and social benefits of eco-cultural tourism in a holistic manner and a vital method of assessing the sustainable development of regional eco-cultural tourism. However, due to the non-profit features of public resources, it is hard to evaluate the performance of eco-cultural tourism in an objective manner through the conventional approach that depends on economic performance as the primary evaluation indicator. Therefore, based on the balanced score card, this paper aims to build a system of performance evaluation indicators custom-tailored to the eco-cultural tourism development in Fujian Province from four aspects, namely, financial performance, public benefits, internal process and learning and growth. By adopting the method of fuzzy comprehensive evaluation, the study intends to objectively assess the economic value, efficiency and public benefits of eco-cultural tourism in Fujian Province. In addition, by adopting the method of Analytic Hierarchy Process (AHP), the study has identified the weights of the performance evaluation indicators, namely, 0.558 for public benefits, 0.122 for financial performance, 0.057 for internal process and 0.263 for learning and growth. Judging from the fuzzy comprehensive evaluation, the effects are found to be at the average level for the eco-cultural tourism development in Fujian Province, scoring between 60 and 74. As shown by the research findings, although Fujian Province is endowed with optimal resources of eco-cultural tourism, further efforts need to be made in exploring and optimizing the building of eco-cultural tourism.